Effect of kinesio Taping on Pain and Disability in Patients with Chronic Low Back Pain - Khaled Z. Fouda; Ibrahim M. Dewir (Journal Riphah College of Rehabilitation Sciences, 2016)
Background: Low back pain (LBP) is a significant public health problem and it is associated with enormous costs to society and disability. Kinesio Taping (KT) is widely used in patients with LBP with different techniques of application.